An Empirical Examination of the Potential Measurement Error in Current Cost Data. - Shriver, Keith A. (The Accounting Review, 1987)
ABSTRACT: The Financial Accounting Standards Board (FASB) is soliciting empirical evidence on the accuracy of price indexes for estimating the current cost of machinery and equipment in compliance with Statement #33. Recent studies indicated that measurement errors in current cost data appear to dominate the potential information content of the Statement #33 disclosures. This study investigates the sign, magnitude, and sources of the potential measurement error in the estimates of current cost generated by alternative levels of specificity of the Producer Price Indexes (PPI). The research method consists of statistical analyses to examine the distributional properties of the PPI estimates compared to the criterion variable of the actual current order price of the assets. The results Indicate that, in general, the measurement error tends to be an overstatement of new current cost. The major sources of measurement error appear to be product mix errors, pricing errors, and inadequate adjustments for quality change. Product mix errors seem to be the dominant factor for Electrical and Miscellaneous Equipment, pricing errors for General Purpose Equipment, and inadequate quality change adjustments for Machine Tools and Special Industry Equipment.